Tufts Grafton Campus Land Stewardship Plan - Von Beren, Brie; Tomko, Mason; LaCombe, Anna; Veldran, Griffin; Edwards, Dahlia (Tufts University. Tisch Library., 2024)
2024 M.A./M.S. in Urban and Environmental Policy and Planning Field Project. Client: Tufts University Office of Sustainability.